Peran Ganda Perempuan dalam Meningkatkan Ekonomi Keluarga: Studi pada Pekerja Pariwisata di Desa Bunga Mekar, Nusa Penida - Ni Kadek Raisa Widirahayu; Luh Indrayani (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyze the dual roles of women in improving family economic conditions, particularly among tourism workers in Bunga Mekar Village, Nusa Penida. A qualitative approach was used, with data collected through observation, in-depth interviews, and documentation. Data collection employed a snowball sampling technique, with the research subjects being women who are both housewives and employed in the tourism sector. The study involved one key informant and seven main informants. Data analysis was conducted using the Miles and Huberman model, which includes data collection, data reduction, data display, and conclusion drawing. The results of the study show that women are able to balance their work and household responsibilities through structured routines and discipline. Despite facing challenges such as physical exhaustion, emotional pressure, and limited skill training from the government, they are still capable of managing their dual roles effectively. In addition to contributing to the family income, women also play a role in managing household finances.